Peluang dan tantangan pengembangan asesmen high order thinking skills dalam pembelajaran matematika di indonesia - Dwi Susanti; Heri Retnawati; Elly Arliani; Latif Irfan (Jurnal Inovasi Pembelajaran Matematika: PowerMathEdu, 2023)
HOTS is a very important aspect to be developed in learning mathematics because in solving non-routine real problems students need critical thinking skills and creative abilities. This literature review aims to provide an overview of the opportunities and challenges of developing high order thinking skills (HOTS) assessments in mathematics learning, especially from a non-technical perspective. Because of the many assessment developments that exist when applied to the assessment of the mathematics learning process. This study was conducted with reference to the method of conducting a literature review proposed by Creswell (2002) in which the study materials used were in the form of journal articles and proceedings. The results of the study indicate that the development of high order thinking skills (HOTS) assessments in mathematics learning has opportunities in terms of the positive influence obtained from the development of the high order thinking skills (HOTS) assessments, while the challenge is how to develop appropriate mathematics learning instruments. with indicators of high order thinking skills (HOTS) questions can be developed that are valid, practical, appropriate, and suitable for use, and maximize the assessment or assessment that will be carried out by the teacher at the end or beginning of learning. Thus, to obtain a positive influence from the development of high order thinking skills (HOTS) assessments in mathematics learning, teachers need to pay attention to these challenges.HOTS merupakan aspek yang sangat penting untuk dikembangkan dalam pembelajaran matematika karena dalam menyelesaikan permasalahan nyata yang tidak rutin siswa memerlukan kemampuan berpikir kritis dan kemampuan kreatif. Kajian literatur ini bertujuan untuk memberikan gambaran mengenai peluang dan tantangan dari pengembangan asesmen high order thinking skills (HOTS) dalam pembelajaran matematika, khususnya dari segi non-teknis. Karena banyaknya pengembangan-pengembangan asesmen yang ada saat diterapkan untuk penilaikan proses pembelajaran matematika. Kajian ini dilakukan dengan mengacu pada metode pelaksanaan kajian literatur yang diajukan oleh Creswell (2002) di mana bahan kajian yang digunakan berupa artikel jurnal dan prosiding. Hasil kajian menunjukkan bahwa pengembangan asesmen high order thinking skills (HOTS) dalam pembelajaran matematika memiliki peluang dalam hal pengaruh yang positif yang diperoleh dari pengembangan asesmen high order thinking skills (HOTS) tersebut, sedangkan tantangan yang ada berupa bagaimana mengembangan instrumen dalam pembelajaran matematika yang sesuai dengan indikator soal high order thinking skills (HOTS) dapat dikembangkan dengan valid, praktis, sesuai, dan layak digunakan, dan memaksimalkan penilaian atau asesmen yang akan dilakukan oleh guru diakhir atau awal pembelajaran. Dengan demikian, untuk memperoleh pengaruh positif dari pengembangan asesmen high order thinking skills (HOTS) pembelajaran matematika, guru perlu memperhatikan tantangan-tantangan tersebut.